Analytical Modelling of High Concentrator Photovoltaic Modules Based on Atmospheric Parameters - Eduardo F. Fernández; F. Almonacid; T. K. Mallick; P. Pérez-Higueras (International Journal of Photoenergy)
The goal of this paper is to introduce a model to predict the maximum power of a high concentrator photovoltaic module. The model is based on simple mathematical expressions and atmospheric parameters. The maximum power of a HCPV module is estimated as a function of direct normal irradiance, cell temperature, and two spectral corrections based on air mass and aerosol optical depth. In order to check the quality of the model, a HCPV module was measured during one year at a wide range of operating conditions. The new proposed model shows an adequate match between actual and estimated data with a root mean square error (RMSE) of 2.67%, a mean absolute error (MAE) of 4.23 W, a mean bias error (MBE) of around 0%, and a determination coefficient (R2) of 0.99.